Characteristics and long-term outcome of echocardiographic super-responders to cardiac resynchronisation therapy: 'real world' experience from a single tertiary care centre. Issue 20 (6th August 2011) - Steffel, Jan; Milosevic, Gligor; Hürlimann, Anja; Krasniqi, Nazmi; Namdar, Mehdi; Ruschitzka, Frank; Lüscher, Thomas F; Duru, Firat; Holzmeister, Johannes; Hürlimann, David
Abstract : Background: The individual benefit from cardiac resynchronisation therapy (CRT) varies largely among patients. Aims: To compare different definitions of echocardiographic super-response to CRT regarding their ability to predict the incidence of adverse events. Methods: Three definitions of super-response to CRT were evaluated in 110 consecutive patients with CRT implantation: (1) an absolute increase in ejection fraction of ≥10%; (2) a decrease in left ventricular end-systolic volume of ≥30%; and (3) a decrease in left ventricular end-diastolic volume of ≥20%. The primary endpoint was a combination of time to death, heart transplantation, ventricular assist device implantation and hospitalisation for heart failure. Secondary endpoints included time to first appropriate implantable cardioverter defibrillator (ICD) discharge during follow-up. Results: All three definitions of super-response were highly predictive of a reduced risk for reaching the primary combined endpoint (3-year estimators: 64%±7% vs 82%±7% for ejection fraction ≥10%; 63%±8% vs 92%±5% for end-systolic volume ≥30%; and 62%±8% vs 94%±4% for end-diastolic volume ≥20%; all p<0.001). In all three analyses, super-responders had a significantly shorter time from diagnosis of heart failure until the time point of CRT implantation. However, even super-responders, independent of the definition, did experience appropriate ICD discharges during follow-up. Conclusions: All three definitions of super-response are highly predictive for a favourable outcome after CRT. However, even patients with pronounced reverse left ventricular remodelling experience appropriate ICD discharges during follow-up.